Triterpenoids as inhibitors of Plasmodium liver-stage development - Ramalhete, Cátia (2012)
Malaria is one of the foremost public health problems in Africa. It is endemic in 90 countries, affecting nearly 40% of the global population. The increasing prevalence of drug-resistant Plasmodium falciparum strains is one of the greatest challenges in malaria control. In order to overcome drug-resistance, new antimalarial drugs are urgently needed. Most of the available antimalarial agents kill blood stage parasites and only a limited number of drugs act on liver stages. In fact, the study of Plasmodium liver stage development (Fig. 1) has been hampered by limitations in the experimental approaches required to quantify hepatocyte infection by the parasite. Therefore, the development of new drugs targeting Plasmodium liver stages represents an important and underexploited site of intervention [1, 2].